Transcript Profiling Analysis and ncRNAs’ Identification of Male-Sterile Systems of Brassica campestris Reveal New Insights Into the Mechanism Underlying Anther and Pollen Development - Zhou, Dong; Chen, Caizhi; Jin, Zongmin; Chen, Jingwen; Lin, Sue; Lyu, Tao; Liu, Dandan; Xiong, Xinpeng; Cao, Jiashu; Huang, Li (Frontiers in Plant Science, 2022)
Male-sterile mutants are useful materials to study the anther and pollen development. Here, whole transcriptome sequencing was performed for inflorescences in three sterile lines of Chinese cabbage (Brassica campestris L. ssp. chinensis Makino, syn. B. rapa ssp. chinensis), the genic male-sterile line (A line), the Polima cytoplasmic male-sterile (CMS) line (P line), and the Ogura CMS line (O line) along with their maintainer line (B line). In total, 7136 DEGs, 361 DELs, 56 DEMs were selected out. Specific regulatory networks related to anther cell differentiation, meiosis cytokinesis, pollen wall formation, and tapetum development were constructed based on the abortion characteristics of male-sterile lines. Candidate genes and lncRNAs related to cell differentiation were identified in sporocyteless P line, sixteen of which were common to the DEGs in Arabidopsis spl/nzz mutant. Genes and lncRNAs concerning cell plate formation were selected in A line that is defected in meiosis cytokinesis. Also, the orthologs of pollen wall formation and tapetum development genes in Arabidopsis showed distinct expression patterns in the three different sterile lines. Among 361 DELs, 35 were predicted to interact with miRNAs, including 28 targets, 47 endogenous target mimics, and five precursors for miRNAs. Two lncRNAs were further proved to be functional precursors for bra-miR156 and bra-miR5718, respectively. Overexpression of bra-miR5718HG in B. campestris slowed down the growth of pollen tubes, caused shorter pollen tubes, and ultimately affected the seed set. Our study provides new insights into molecular regulation especially the ncRNA interaction during pollen development in Brassica crops.